On the relationship between force reduction, loading rate and energy absorption in athletics tracks. (June 2018) - Andena, Luca; Ciancio, Antonio; Briatico-Vangosa, Francesco; Mariani, Stefano; Pavan, Andrea
In this work, finite element simulations of typical sports surfaces were performed to evaluate parameters, such as the loading rate and the energy absorbed by the surface, in relation to its characteristics (surface structure and material properties). Hence, possible relations between these quantities and the standard parameters used to characterize the shock absorbing characteristics of the athletics track (in particular, its force reduction) were investigated. The samples selected for this study were two common athletics tracks and a sheet of natural rubber. They were first characterized by quasi-static compression tests; their mechanical properties were extrapolated to the strain rate of interest and their dependence on the level of deformation was modelled with hyperelastic constitutive equations. Numerical simulations were carried out for varying sample thicknesses to understand the influence of track geometry on force reduction, loading rate and stored energy. A very good correlation was found between force reduction and the other relevant parameters, with the exception of the loading rate at the beginning of the impact.